DISPLACEMENT AND LOAD IN THE NODES OF THE MINE TRAWL ACTUATOR MECHANISM DURING AN EXPLOSION - Kryzhanivskyi, E. I.; Artym, V. I.; Senchishak, V. M.; Yanitskyi, Yu. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
It has been established that the development of an analytical model for determining the displacements and loads of the actuator nodes during an explosion is relevant, has theoretical and practical value. Based on the analysis of the latest research sources and publications, a conclusion was made about the insufficient attention to the impact of the blast wave on the actuator nodes. Therefore, the purpose of the work was to develop an analytical model for assessing the displacements and loads of the actuators taking into account the impact of the explosion. To develop the model, a mine trawl roller mechanism was proposed. The dependences of the kinematic parameters of the links of the roller mechanism, which falls into the explosion zone, on the parameters of the blast wave were obtained. A force analysis of the mine trawl mechanism was carried out. It was clarified what external loads arise on the links of the mechanisms and how they are redistributed through the movable joints to the body links of the vehicle. An equation was proposed to determine the angle of inclination of the protective shield from the condition of stabilizing the vertical stability of the machine unit. The results obtained make it possible to analyze the displacements and loads of the links of real mine trawl actuators in order to optimize their parameters during design.